Influence of residual bone height and sinus width on the outcome of maxillary sinus bone augmentation using anorganic bovine bone - Pignaton, Túlio Bonna [UNESP]; Wenzel, Ann; Ferreira, Carlos Eduardo de Almeida; Borges Martinelli, Carolina; Oliveira, Guilherme J. P. L. [UNESP]; Marcantonio, Elcio [UNESP]; Spin-Neto, Rubens (Wiley, 2019)
Objective: To evaluate the influence of the posterior residual bone height and sinus width on the outcome of maxillary sinus bone augmentation using anorganic bovine bone. Material and methods: Bilateral sinus bone augmentation was performed using anorganic bovine bone in 20 patients with residual bone height <2 mm in at least one site on each side. Trephine samples were removed at the implant insertion site 8 months after the grafting procedure, and histological and histomorphometric analyses were performed to examine the relative amount (%) of new bone, anorganic bovine bone, and soft tissue in the grafted area. Based on cone beam computed tomography evaluation, the sites of implant insertion were classified according to sinus width into narrow, average, and wide, and according to residual bone height into ≤2 and >2 mm. Results: A total of 146 implants were installed and 103 biopsies were evaluated. New bone formation in sites classified as narrow (69 sites), average (19 sites), and wide (15 sites) was 28.5% ± 9.24, 28.9% ± 8.61, and 30.3% ± 7.80, respectively. The mean posterior maxillary residual bone height was 4.0 ± 2.43 mm, and 26 and 77 sites were classified as ≤2 and >2 mm, respectively. New bone formation was 26.2% ± 9.10 and 29.8% ± 8.67 for residual bone height ≤2 and >2 mm, respectively. The differences were non-significant. Conclusions: Within the limitations of the present study, posterior residual bone height and sinus width were not factors with influence on new bone formation in sinuses grafted exclusively with anorganic bovine bone after 8 months of healing.
Keywords: bone formation; bone substitutes; clinical trial; sinus floor augmentation